(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
Power quality is an important field in an electrical power system. Current harmonic pollution can be a problem to the system directly. Source of harmonic can be produced from the electrical non-linear load, and it became increasing each day to a low voltage system. Non-linear loads were due to the semiconductor component in electrical equipment. Research on this problem nowadays is declining due to awareness of this matter. The research was conducted on a low voltage system with a balanced three-phase source equipped with a non-linear load. To study cable sizing, a sequence of fundamental current applied with several methods.